2020
DOI: 10.1093/rap/rkaa033
|View full text |Cite
|
Sign up to set email alerts
|

Psoriatic arthritis epidemiology, comorbid disease profiles and risk factors: results from a claims database analysis

Abstract: Abstract Objective Psoriasis (PsO) is a systemic inflammatory disease often accompanied by comorbid diseases, including metabolic syndrome, cardiovascular diseases and depression. Up to 41% of PsO patients develop psoriatic arthritis (PsA), making it one of the most relevant manifestations. A large health claims data set was analyzed to determine the rate of PsA development in PsO patients. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 36 publications
0
11
0
4
Order By: Relevance
“…Indeed, symptoms and signs of prodromal and early PsA may be subtle and fluctuating, as shown by a recent German retrospective analysis that found that unspecific arthritic symptoms (such as acute rheumatism) precede the development of PsA. 12 Similarly, a Bayesian network model found that the musculoskeletal symptoms that predict the development of PsA in psoriatic patients are non-specific arthritis, fatigue, swelling, arthralgia, myalgia and pain in the back, finger, hand and knee. 13 In addition, inflammatory markers are commonly normal or only minimally elevated in early PsA.…”
Section: Clinical Manifestationsmentioning
confidence: 98%
“…Indeed, symptoms and signs of prodromal and early PsA may be subtle and fluctuating, as shown by a recent German retrospective analysis that found that unspecific arthritic symptoms (such as acute rheumatism) precede the development of PsA. 12 Similarly, a Bayesian network model found that the musculoskeletal symptoms that predict the development of PsA in psoriatic patients are non-specific arthritis, fatigue, swelling, arthralgia, myalgia and pain in the back, finger, hand and knee. 13 In addition, inflammatory markers are commonly normal or only minimally elevated in early PsA.…”
Section: Clinical Manifestationsmentioning
confidence: 98%
“…Patients with specific psoriasis phenotypes (scalp, inverse, and nail psoriasis) and risk factors such as obesity, family history of PsA, and severe psoriasis should receive particular attention since they have greater chances of developing PsA [ 4 ]. Additionally, as shown by a retrospective analysis of data from the Institute of Applied Health Research Berlin, patients with psoriasis who experienced acute rheumatism or pain in unspecific joints are at an increased risk of developing PsA as well [ 5 ]. Dermatologists should particularly assess complaints of joint pain, stiffness, and swelling, with particular attention to their onset, duration, and relationship to exercise.…”
Section: Introductionmentioning
confidence: 99%
“…Psoriasis is an inflammatory cutaneous disorder with prevalence up to 3% of people in industrialized countries ( 1 ). Originally described as a skin and/or articular pathology, psoriasis appears as a disease involving other tissue damage.…”
Section: Introductionmentioning
confidence: 99%